A critical analysis of the referral system under the international criminal court - Mapiye, Patrick (Midlands State University, 2017)
This research sought to establish whether the referral system under the Rome Statute of the International Criminal Court is fulfilling the international community‟s quest to end impunity under international criminal law. The research provides a critical analysis of the referral system looking at its application in reality by the various actors so empowered to implement it. It is the argument of this research that the referral system has been hijacked by selective justice, revenge, politics and victor‟s justice rendering the referral system ineffective. Further, it is argued that the perceived injustice and disillusionment faced by State parties over the manner in which the referral system is being implemented is tearing the ICC apart unless radical changes are done to reform the status quo. The research also proffered some recommendations, though not exhaustive, to better the referral system.